Water-based single-component coating for container and preparation method of water-based single-component coating

By adopting a water-based single-component coating system, using modified resins and fillers to form a complex and stable three-dimensional network structure, the problems of corrosion resistance and short weather resistance of container coatings in high temperature and high humidity environments are solved, and the comprehensive coating performance is achieved Improve and reduce production costs.

CN119432229AInactive Publication Date: 2025-02-14SHANGHAI HAOLI PAINT CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510040086.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing container coatings have poor corrosion resistance in high temperature and high humidity environments, short weathering time, and traditional coatings have many construction times, high energy consumption, high cost, low performance and hardness, poor stain resistance, and poor water resistance in the early stage.

Method used

Using an aqueous single-component coating system, including aqueous acrylic silica resin, modified aqueous acrylic resin, modified aqueous epoxy resin, anti-rust pigment, coloring pigment, modified filler, cosolvent and additives, through modified resin and filler The use of the coating forms a complex and stable three-dimensional network structure, improving the aging resistance, salt spray resistance and initial water resistance of the coating.

Benefits of technology

Reduces the number of coatings and drying times, shortens the production cycle, reduces production costs, improves the hardness, wear resistance, stain resistance, initial water resistance and salt spray resistance of the coating, and enhances the stability of the coating Sex and compactness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of coatings, and particularly relates to a water-based single-component coating for containers and a preparation method thereof.The water-based single-component coating for containers comprises, by weight, 15-20 parts of water, 40-45 parts of water-based acrylic silicon resin, 15-20 parts of modified water-based acrylic resin, 8-13 parts of modified water-based epoxy resin and 10-15 parts of anti-rust pigment. The coating is prepared from, by weight, 10-15 parts of coloring pigment, 10-15 parts of modified filler, 3-5 parts of cosolvent and 3-5 parts of auxiliaries. The coating is excellent in comprehensive performance and can be used as a coating for containers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, and in particular to a water-based single-component coating for a container and a preparation method thereof. Background Art

[0002] In order to protect the metal surface of the container, extend its service life, and ensure its performance under various environmental conditions, it is usually necessary to use coatings on the surface of the container.

[0003] The conventional container coating technology generally adopts a water-based epoxy zinc-rich primer, a second water-based epoxy primer and a water-based acrylic topcoat system. Not only does it require many coatings, consumes a lot of energy, takes a long time, and has a high final cost, but it also has low hardness, poor stain resistance, and poor initial water resistance. These deficiencies arise because it requires three spraying operations and three dryings in the drying room, and each drying takes a certain amount of time to ensure that it is well dried. In terms of performance, the water-based acrylic topcoat itself has a low TG, strong water absorption, and a soft paint film. Pollutants are easily adhered to it when the temperature is high, and if it is not dried sufficiently, it will bubble when it rains.

[0004] At present, water-based coatings that can replace the traditional container secondary primer and topcoat system are gaining more and more attention. However, compared with traditional coatings, the coatings used in containers face multiple technical challenges due to their special use environment. These problems not only affect the performance of the coatings, but may also shorten the service life of the container: 1. Corrosion resistance: Containers are often exposed to high-salt environments during ocean transportation, and salt spray can cause rapid corrosion of metal surfaces. The high temperature and high humidity environment in tropical and subtropical areas will accelerate the corrosion of metals, and the coatings need to maintain good protective properties under these conditions. 2. Weather resistance: Long-term exposure to ultraviolet rays may cause the coating to powder, crack, fade and other problems. High-performance coatings need to have good resistance to ultraviolet aging. Containers are used in different climatic conditions and the temperature changes frequently. The coatings need to be able to withstand extreme temperature changes and maintain the stability of physical and chemical properties. 3. Mechanical properties: Wear resistance: Containers are often subjected to friction and impact during loading and unloading and transportation, and the coatings need to have good wear resistance and impact resistance. Flexibility: Containers may be slightly deformed during transportation, and the coatings need to have a certain degree of flexibility to adapt to these deformations without cracking. 4. Chemical stability: Chemical resistance: Various chemicals may be loaded in containers, and the coating needs to be able to resist corrosion from chemicals such as acids, alkalis, and solvents. Oil resistance: Some cargoes may contain grease, and the coating needs to have good oil resistance to prevent grease penetration and softening. 5. Low VOC: Environmental regulations have strict restrictions on the content of volatile organic compounds (VOC) in coatings.

[0005] In the prior art, a product with excellent weather resistance and salt spray resistance is prepared by using a water-based acrylic silicone emulsion and a water-based epoxy emulsion as a film-forming substance, and is used as a container coating. However, the corrosion resistance of this coating is not ideal under high temperature and high humidity conditions, and the weather resistance time is short.

[0006] Therefore, there is an urgent need for a water-based one-component coating for containers and a preparation method thereof. Summary of the invention

[0007] The purpose of the present invention is to provide a water-based one-component coating for containers and a preparation method thereof. The coating prepared by the present invention can replace the secondary primer and topcoat system of containers in the traditional sense, which not only reduces the number of coating times and shortens the drying time, but also reduces the time for workpieces to be offline, greatly shortens the production cycle of workpieces, reduces production costs, and has excellent comprehensive performance.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: A water-based single-component coating for a container, comprising the following components in parts by weight: 15-20 parts of water, 40-45 parts of water-based acrylic silicone resin, 15-20 parts of modified water-based acrylic resin, 8-13 parts of modified water-based epoxy resin, 10-15 parts of anti-rust pigment, 10-15 parts of coloring pigment, 10-15 parts of modified filler, 3-5 parts of cosolvent, and 3-5 parts of auxiliary agent; the auxiliary agent comprises a dispersant, a defoamer, a wetting agent, and a thickener in a weight ratio of 1: (1.2-1.3): (0.5-0.7): (1-1.2); The preparation method of the modified waterborne acrylic resin comprises the following steps in parts by weight: S1, 400-420 parts of mixed monomers, 25-35 parts of 3-(trimethoxysilyl)propyl acrylate, 40-50 parts of ethylene urea ethoxy methacrylate, 13-17 parts of di-tert-butyl peroxide, and 9-12 parts of dodecyl mercaptan are mixed, and the mixture is added dropwise to 250-300 parts of ethylene glycol ethyl ether at a temperature of 140-145° C. The addition time is 3.2-3.6 hours. After the addition is completed, the mixture is reacted at 140-145° C. for 4-6 hours to obtain a pre-modified acrylate resin; S2, 120-130 parts of ethylene glycol ethyl ether, 100 parts of water-based epoxy resin, 0.5-0.7 parts of dimethylethanolamine, and 20-30 parts of dimethylol propionic acid are mixed, the temperature is raised to 110-120° C., and the reaction is performed for 5-7 hours to obtain a semi-open-ring epoxy resin; S3, mixing the pre-modified acrylate resin prepared in S1 and the semi-open-ring epoxy resin prepared in S2, heating to 130-135° C., reacting for 2-3 hours, cooling to 60-65° C., adding 50-60 parts of triethylamine, and obtaining a modified waterborne acrylic resin.

[0009] Furthermore, the mixed monomer is isobornyl methacrylate, hydroxypropyl methacrylate, and methacrylic acid in a weight ratio of 1: (1.2-1.4): (0.5-0.7).

[0010] Water-based acrylic silicone resin is one of the main raw materials of single-component coatings at present, but the coatings prepared by using it on the market cannot meet the requirements of aging resistance of container coatings. The present invention can improve the aging resistance of coatings by adding modified water-based acrylic resins into the system. Because 3-(trimethoxysilyl)propyl acrylate is introduced into the modified water-based acrylic resin, and the secondary amine introduced into ethylene urea ethoxy methacrylate can react with the epoxy group in the semi-open ring epoxy resin, the coating can form a more complex and stable three-dimensional network structure, thereby improving the aging resistance of the coating.

[0011] Furthermore, the preparation method of the modified waterborne epoxy resin comprises the following steps, measured by weight: (1) Mix 30-32 parts of phenolic epoxy resin, 0.5-0.8 parts of tetra-n-butylammonium bromide and 0.1-0.2 parts of hydroquinone, raise the temperature to 90-95°C, and dropwise add 40-50 parts of a mixed solution of heptafluorobutyric acid and 12-15 parts of methacrylic acid for 1-2 hours. After the dropwise addition is completed, raise the temperature to 115-120°C and react for 5-7 hours to obtain a prepolymer; (2) Mix 35-40 parts of prepolymer and 5-10 parts of maleic anhydride, react at 95-100°C for 3-4 hours, add 5-8 parts of triethylamine, stir for 50-60 minutes, add 50-55 parts of deionized water, stir at 50-55°C for 2.0-2.5 hours, and cool to obtain a modified waterborne epoxy resin.

[0012] In the actual use of containers, the coating needs to withstand the test of various humid environments in a short time, so it is very important to measure the initial water resistance of container coatings. The present invention attempts to add water-based epoxy resin, but the effect is not ideal. The present invention can improve the initial water resistance of the coating by modifying the water-based epoxy resin. It is mainly through the introduction of fluorinated groups and maleic anhydride to react with the epoxy groups in the prepolymer to form more ester bonds, and form a high crosslinking density with other components in the system. Through synergistic effects, the initial water resistance of the coating can be improved.

[0013] Furthermore, the preparation method of the modified filler comprises the following steps, measured by weight: (1) mixing nano-lanthanum oxide, nano-aluminum oxide and nano-silicon dioxide to obtain a mixed filler; (2) Mix 1 part of mixed filler, 8-10 parts of anhydrous ethanol and 0.1-0.3 parts of silane coupling agent KH570, stir and react at 60-65°C for 5-7h, filter, wash and dry to obtain silane-modified filler; (3) Mix 10-15 parts of anhydrous ethanol, 1 part of silane-modified filler, 0.03-0.05 parts of azobisisobutyronitrile, and 0.2-0.3 parts of glycidyl methacrylate, heat and stir at 60-65° C. for 7-9 hours, filter, wash, and dry to obtain a modified filler.

[0014] Furthermore, the weight ratio of nano-lanthanum oxide, nano-aluminum oxide and nano-silicon dioxide is (1.3-1.5):1:(0.4-0.7).

[0015] Furthermore, the particle size of nano-alumina is 15-20nm and the specific surface area is 150-200m 2 / g; the particle size of nano-silicon dioxide is 10-20nm, and the specific surface area is 70-100m 2 / g; the particle size of nano lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g.

[0016] Containers are often exposed to high-salt environments during ocean transportation, and salt spray can cause rapid corrosion of metal surfaces. In order to improve the salt resistance of the coating, the present invention attempts to add fillers, but the effect is not ideal. The present invention can improve the salt resistance of the coating at room temperature by modifying the filler. This is mainly because the modified coating has better compatibility with other components in the system, and has better compatibility and bonding with the polymer matrix, reduces the agglomeration of fillers in the coating, and improves the uniformity and density of the coating; at the same time, it can improve the cross-linking density of other components and improve the density of the coating.

[0017] And when the modified waterborne acrylic resin uses a specific amount of mixed monomers, 3-(trimethoxysilyl)propyl acrylate, ethylene urea ethoxy methacrylate, and fillers with specific parameters, the salt resistance at high temperature can be improved. Mainly under this condition, the modified waterborne acrylic resin forms a more stable three-dimensional network structure, and the high specific surface area and good dispersibility of the nanofiller can fill the tiny pores in the coating, improve the density of the coating, and improve the salt resistance at high temperature. .

[0018] Furthermore, the anti-rust pigment is aluminum zinc phosphate, which is purchased from Hebei Kuanting New Material Technology Co., Ltd.

[0019] Furthermore, the coloring pigment is titanium dioxide. The particle size of titanium dioxide is 10-20nm, and the specific surface area is 80-90m 2 / g.

[0020] Furthermore, the dispersant is BYK-190.

[0021] Furthermore, the leveling agent is BYK-378.

[0022] Furthermore, the thickener is XS83. Brand: Arkema.

[0023] Furthermore, the defoaming agent is Digo 901W.

[0024] Furthermore, the cosolvent is dipropylene glycol methyl ether acetate.

[0025] The present invention also provides a method for preparing a water-based one-component coating for a container, comprising the following steps: (1) Weigh each component according to its weight; (2) Add defoamer and dispersant into water under low-speed stirring and stir for 5-10 minutes; (3) Add coloring pigment, anti-rust pigment and modified filler under stirring, stir for 15-30 minutes after adding, and disperse at high speed. Stop dispersing after reaching the required fineness and transfer to the paint mixing tank; (4) Add the remaining components while stirring and stir for 0.5-1h to obtain a water-based one-component coating for containers.

[0026] The beneficial effects of the present invention are: (1) The present invention replaces the traditional waterborne epoxy primer and waterborne acrylic topcoat system for containers, which not only reduces the number of coatings and drying time, but also reduces the time it takes for workpieces to come off the production line, greatly shortening the production cycle of workpieces and reducing production costs; (2) The present invention enables the supporting system to have low surface energy, good hardness and wear resistance, excellent stain resistance, excellent initial water resistance, and good salt spray resistance.

[0027] (3) The acrylic silicone resin used in the present invention is moisture-cured or oven-dried, which increases the hardness of the coating and enhances its stain resistance. The resulting coating has a lower surface energy, reduces the hydrophilicity of the coating, and solves the problem of blistering caused by poor drying.

[0028] (4) The present invention can improve the aging resistance of the coating by adding a modified waterborne acrylic resin into the system.

[0029] (5) The present invention can improve the initial water resistance of the coating by modifying the water-based epoxy resin.

[0030] (6) The present invention can improve the salt resistance of the coating at room temperature by modifying the filler.

[0031] (7) When the modified waterborne acrylic resin uses a specific amount of mixed monomers, 3-(trimethoxysilyl)propyl acrylate, ethylene urea ethoxy methacrylate, and fillers with specific parameters, the salt resistance at high temperature can be improved. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The raw materials of the present invention are all commercially available products, provided by the following manufacturers: Water-based acrylic silicone resin, Kashima Chemical Co., Ltd.

[0034] 3-(Trimethoxysilyl)propyl acrylate, CAS: 4369-14-6. Wuhan Woxuan Technology Co., Ltd.

[0035] Ethylene urea ethoxy methacrylate, CAS No. 86261-90-7. Zhongshan Dixin Chemical Co., Ltd.

[0036] Water-based epoxy resin, brand: Baling Petrochemical, model CYDW-100.

[0037] Phenolic epoxy resin, Huangshan Aoshengyuan New Material Technology Co., Ltd., model SR-F51 water-soluble phenolic epoxy resin.

[0038] The anti-rust pigment is aluminum zinc phosphate, which was purchased from Hebei Kuanting New Material Technology Co., Ltd.

[0039] The coloring pigment is titanium dioxide. The particle size of titanium dioxide is 10-20nm and the specific surface area is 80-90m 2 / g.

[0040] The dispersant is BYK-190.

[0041] The leveling agent is BYK-378.

[0042] Thickener is XS83. Brand: Arkema.

[0043] The defoaming agent is Digo 901W.

[0044] The cosolvent is dipropylene glycol methyl ether acetate.

[0045] Wetting agent TEGO4100.

[0046] Example 1 The present embodiment provides a water-based one-component coating for a container, comprising the following components in parts by weight: 17 parts of water, 42 parts of water-based acrylic silicone resin, 18 parts of modified water-based acrylic resin, 10 parts of modified water-based epoxy resin, 13 parts of anti-rust pigment, 12 parts of coloring pigment, 14 parts of modified filler, 4 parts of cosolvent, and 4 parts of auxiliary agent; the auxiliary agent comprises a dispersant, a defoamer, a wetting agent, and a thickener in a weight ratio of 1:1.2:0.6:1.1 The preparation method of the modified waterborne acrylic resin comprises the following steps in parts by weight: S1, 410 parts of mixed monomers, 30 parts of 3-(trimethoxysilyl)propyl acrylate, 45 parts of ethylene urea ethoxy methacrylate, 14 parts of di-tert-butyl peroxide, and 10 parts of dodecyl mercaptan were mixed, and the mixture was added dropwise to 270 parts of ethylene glycol ethyl ether at a temperature of 142° C. The addition time was 3.5 hours. After the addition was completed, the mixture was reacted at 142° C. for 5 hours to obtain a pre-modified acrylate resin; The mixed monomers are isobornyl methacrylate, hydroxypropyl methacrylate and methacrylic acid in a weight ratio of 1:1.3:0.6.

[0047] S2, 125 parts of ethylene glycol ethyl ether, 100 parts of water-based epoxy resin, 0.6 parts of dimethylethanolamine, and 25 parts of dimethylol propionic acid were mixed, the temperature was raised to 115° C., and the reaction was performed for 6 hours to obtain a semi-open-ring epoxy resin; S3, mixing the pre-modified acrylate resin prepared in S1 and the semi-open-ring epoxy resin prepared in S2, heating to 132° C., reacting for 2.5 hours, cooling to 62° C., adding 55 parts of triethylamine, and obtaining a modified waterborne acrylic resin.

[0048] The preparation method of the modified waterborne epoxy resin comprises the following steps by weight: (1) 31 parts of phenolic epoxy resin, 0.7 parts of tetra-n-butylammonium bromide and 0.15 parts of hydroquinone were mixed, the temperature was raised to 92°C, and a mixture of 45 parts of heptafluorobutyric acid and 13 parts of methacrylic acid was added dropwise for 1.5 hours. After the addition was completed, the temperature was raised to 118°C and reacted for 6 hours to obtain a prepolymer; (2) Mix 37 parts of prepolymer and 8 parts of maleic anhydride, react at 98°C for 3.6 hours, add 7 parts of triethylamine, stir for 55 minutes, add 52 parts of deionized water, stir at 52°C for 2.3 hours, and cool to obtain a modified waterborne epoxy resin.

[0049] The preparation method of the modified filler comprises the following steps by weight: (1) mixing nano-lanthanum oxide, nano-aluminum oxide and nano-silicon dioxide in a weight ratio of 1.4:1:0.6 to obtain a mixed filler; (2) Mix 1 part of mixed filler, 9 parts of anhydrous ethanol and 0.2 parts of silane coupling agent KH570, stir and react at 62°C for 6 hours, filter, wash and dry to obtain a silane-modified filler; (3) 13 parts of anhydrous ethanol, 1 part of silane-modified filler, 0.04 parts of azobisisobutyronitrile, and 0.25 parts of glycidyl methacrylate were mixed, heated at 63° C. with stirring for 8 h, filtered, washed, and dried to obtain a modified filler.

[0050] The particle size of nano-alumina is 15-20nm and the specific surface area is 150-200m 2 / g; the particle size of nano-silicon dioxide is 10-20nm, and the specific surface area is 70-100m 2 / g; the particle size of nano lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g. All from Beijing Dekedaojin Technology Co., Ltd.

[0051] The method for preparing the water-based one-component coating for a container comprises the following steps: (1) Weigh each component according to its weight; (2) Add defoamer and dispersant into water under low-speed stirring and stir for 8 minutes; (3) Add coloring pigment, anti-rust pigment and modified filler under stirring, stir for 20 minutes after adding, and disperse at high speed. Stop dispersing after reaching the required fineness and transfer to the paint mixing tank; (4) Add the remaining components while stirring and stir for 0.7 h to obtain a water-based one-component coating for containers.

[0052] Example 2 The present embodiment provides a water-based one-component coating for a container, comprising the following components in parts by weight: 15 parts of water, 45 parts of water-based acrylic silicone resin, 15 parts of modified water-based acrylic resin, 13 parts of modified water-based epoxy resin, 10 parts of anti-rust pigment, 15 parts of coloring pigment, 10 parts of modified filler, 5 parts of cosolvent, and 3 parts of additives; the additives include a dispersant, a defoamer, a wetting agent, and a thickener in a weight ratio of 1:1.2:0.5:1 The preparation method of the modified waterborne acrylic resin comprises the following steps in parts by weight: S1, 420 parts of mixed monomers, 25 parts of 3-(trimethoxysilyl)propyl acrylate, 50 parts of ethylene urea ethoxy methacrylate, 13 parts of di-tert-butyl peroxide, and 12 parts of dodecyl mercaptan were mixed, and added dropwise to 300 parts of ethylene glycol ethyl ether at a temperature of 140° C. The dropping time was 3.2 hours. After the dropping was completed, the mixture was reacted at 145° C. for 4 hours to obtain a pre-modified acrylate resin; The mixed monomers are isobornyl methacrylate, hydroxypropyl methacrylate and methacrylic acid in a weight ratio of 1:1.2:0.5.

[0053] S2, 130 parts of ethylene glycol ethyl ether, 100 parts of water-based epoxy resin, 0.7 parts of dimethylethanolamine, and 20 parts of dimethylolpropionic acid were mixed, the temperature was raised to 120° C., and the reaction was performed for 7 hours to obtain a semi-open-ring epoxy resin; S3, mixing the pre-modified acrylate resin prepared in S1 and the semi-open-ring epoxy resin prepared in S2, heating to 135° C., reacting for 3 hours, cooling to 60° C., adding 50 parts of triethylamine, and obtaining a modified waterborne acrylic resin.

[0054] The preparation method of the modified waterborne epoxy resin comprises the following steps by weight: (1) 32 parts of phenolic epoxy resin, 0.5 parts of tetra-n-butylammonium bromide and 0.2 parts of hydroquinone were mixed, the temperature was raised to 90°C, and a mixed solution of 50 parts of heptafluorobutyric acid and 12 parts of methacrylic acid was added dropwise for 2 hours. After the addition was completed, the temperature was raised to 120°C and reacted for 5 hours to obtain a prepolymer; (2) Mix 40 parts of prepolymer and 5 parts of maleic anhydride, react at 100°C for 3 hours, add 8 parts of triethylamine, stir for 50 minutes, add 55 parts of deionized water, stir at 50°C for 2.5 hours, and cool to obtain a modified waterborne epoxy resin.

[0055] The preparation method of the modified filler comprises the following steps by weight: (1) mixing nano-lanthanum oxide, nano-aluminum oxide and nano-silicon dioxide in a weight ratio of 1.3:1:0.7 to obtain a mixed filler; (2) Mix 1 part of mixed filler, 10 parts of anhydrous ethanol and 0.1 parts of silane coupling agent KH570, stir and react at 65°C for 5 hours, filter, wash and dry to obtain a silane-modified filler; (3) Mix 15 parts of anhydrous ethanol, 1 part of silane-modified filler, 0.03 parts of azobisisobutyronitrile, and 0.3 parts of glycidyl methacrylate, heat and stir at 60°C for 9 hours, filter, wash, and dry to obtain a modified filler.

[0056] The particle size of nano-alumina is 15-20nm and the specific surface area is 150-200m 2 / g; the particle size of nano-silicon dioxide is 10-20nm, and the specific surface area is 70-100m 2 / g; the particle size of nano lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g.

[0057] The method for preparing the water-based one-component coating for a container comprises the following steps: (1) Weigh each component according to its weight; (2) Add defoamer and dispersant into water under low-speed stirring and stir for 10 minutes; (3) Add coloring pigment, anti-rust pigment and modified filler under stirring, stir for 15 minutes after adding, and disperse at high speed. Stop dispersing after reaching the required fineness and transfer to the paint mixing tank; (4) Add the remaining components while stirring and stir for 1 hour to obtain a water-based one-component coating for containers.

[0058] Comparative Example 1 The difference between this comparative example and Example 1 is that a water-based one-component coating for a container comprises the following components in parts by weight: 17 parts of water, 50 parts of water-based acrylic silicone resin, 10 parts of modified water-based acrylic resin, 5 parts of modified water-based epoxy resin, 13 parts of anti-rust pigment, 12 parts of coloring pigment, 17 parts of modified filler, 4 parts of cosolvent, and 4 parts of additive.

[0059] Comparative Example 2 The difference between this comparative example and Example 1 is that 3-(trimethoxysilyl)propyl acrylate is not used.

[0060] The preparation method of the modified waterborne acrylic resin comprises the following steps: S1, 410 parts of mixed monomers, 75 parts of ethylene urea ethoxy methacrylate, 14 parts of di-tert-butyl peroxide, and 10 parts of dodecyl mercaptan were mixed, and the mixture was added dropwise to 270 parts of ethylene glycol ethyl ether at a temperature of 142° C. The addition time was 3.5 hours. After the addition was completed, the mixture was reacted at 142° C. for 5 hours to obtain a pre-modified acrylate resin; The mixed monomers are isobornyl methacrylate, hydroxypropyl methacrylate and methacrylic acid in a weight ratio of 1:1.3:0.6.

[0061] S2, 125 parts of ethylene glycol ethyl ether, 100 parts of water-based epoxy resin, 0.6 parts of dimethylethanolamine, and 25 parts of dimethylol propionic acid were mixed, the temperature was raised to 115° C., and the reaction was performed for 6 hours to obtain a semi-open-ring epoxy resin; S3, mixing the pre-modified acrylate resin prepared in S1 and the semi-open-ring epoxy resin prepared in S2, heating to 132° C., reacting for 2.5 hours, cooling to 62° C., adding 55 parts of triethylamine, and obtaining a modified waterborne acrylic resin.

[0062] Comparative Example 3 The difference between this comparative example and Example 1 is that the mixed monomers are isobornyl methacrylate, hydroxypropyl methacrylate and methacrylic acid in a weight ratio of 1:1:1.

[0063] Comparative Example 4 The difference between this comparative example and Example 1 is that the modified waterborne epoxy resin is replaced by phenolic epoxy resin. Phenolic epoxy resin, Huangshan Aoshengyuan New Material Technology Co., Ltd., model SR-F51 water-soluble phenolic epoxy resin.

[0064] Comparative Example 5 The difference between this comparative example and Example 1 is that the preparation method of the modified filler comprises the following steps: (1) mixing nano-lanthanum oxide, nano-aluminum oxide and nano-silicon dioxide in a weight ratio of 1.4:1:0.6 to obtain a mixed filler; (2) Mix 1 part of mixed filler, 9 parts of anhydrous ethanol and 0.2 parts of silane coupling agent KH570, stir and react at 62°C for 6 hours, filter, wash and dry to obtain a modified filler.

[0065] Comparative Example 6 The difference between this comparative example and Example 1 is that the particle size of nano-alumina is 20-30nm, and the specific surface area is 50-100m 2 / g; the particle size of nano-silicon dioxide is 50-60nm, and the specific surface area is 30-50m 2 / g. The particle size of nano lanthanum oxide is 70nm-90nm, and the specific surface area is 5-10m 2 / g.

[0066] Performance Testing The performance of the water-based one-component container coatings prepared in Examples 1-2 and Comparative Examples 1-6 was tested.

[0067] According to the container coating test standard, the coating prepared in Example 1-2 was tested for indicators. The results are shown in Table 1.

[0068] 2. The test specimens were prepared by spraying the water-based single-component coating on the surface of the container steel. The dry film thickness of the coating was 100±10μm. The performance test was carried out. The test results are shown in Table 2.

[0069] Initial water resistance, test standard: GB / T1766-2008: Initial water resistance test method, after spraying and forced drying for 1 hour, put the coating sample into water, take it out after the specified time, absorb the water marks with filter paper, and immediately check for rust, shedding, etc. Then, place it under standard conditions for 24 hours, and check for discoloration, blistering, rust, and shedding.

[0070] Bending performance, test standard: GB / T6742-2007.

[0071] Resistance to liquid media, GB / T9274-1988.

[0072] Resistance to artificial climate accelerated aging test, GB / T14522-2008.

[0073] Salt spray resistance, GB / T1771-2007.

[0074] The present invention replaces the traditional water-based epoxy secondary primer and water-based acrylic topcoat system of containers, which not only reduces the number of coating times and drying time, but also reduces the time for workpieces to come off the production line, greatly shortens the production cycle of the workpieces, and reduces production costs; the present invention enables the supporting system to have lower surface energy, good hardness and wear resistance, excellent stain resistance, excellent initial water resistance, and good salt spray resistance.

[0075] It can be seen from the above performance test results that the coatings prepared in Examples 1-2 have excellent comprehensive performance, which is mainly due to the synergistic compounding of multiple components.

[0076] However, the comparative examples are significantly worse than the embodiments in terms of corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the ratio of the components is changed, and it can be seen that the comprehensive effect of the coating is reduced. In comparative example 2, 3-(trimethoxymethylsilyl)propyl acrylate is not used to prepare the modified water-based acrylic resin. From the results, it can be seen that the aging resistance is reduced, and the salt resistance at high temperature is reduced; the ratio of the mixed monomers in comparative example 3 is different, and the bending performance is reduced; in comparative example 4, the epoxy resin is not modified, and the initial waterproof performance is reduced. In comparative example 5, the filler modification method is different, and the salt resistance of the coating at room temperature is reduced. In comparative example 6, the parameters of the filler are different, and the high-temperature salt resistance of the coating is reduced. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0077] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A water-based one-component coating for containers, characterized in that: The invention comprises the following components in parts by weight: 15-20 parts of water, 40-45 parts of water-based acrylic silicone resin, 15-20 parts of modified water-based acrylic resin, 8-13 parts of modified water-based epoxy resin, 10-15 parts of anti-rust pigment, 10-15 parts of coloring pigment, 10-15 parts of modified filler, 3-5 parts of cosolvent, and 3-5 parts of auxiliary agent; the auxiliary agent comprises a dispersant, a defoamer, a wetting agent and a thickener in a weight ratio of 1: (1.2-1.3): (0.5-0.7): (1-1.2); The preparation method of the modified waterborne acrylic resin comprises the following steps in parts by weight: S1, 400-420 parts of mixed monomers, 25-35 parts of 3-(trimethoxysilyl)propyl acrylate, 40-50 parts of ethylene urea ethoxy methacrylate, 13-17 parts of di-tert-butyl peroxide, and 9-12 parts of dodecyl mercaptan are mixed, and the mixture is added dropwise to 250-300 parts of ethylene glycol ethyl ether at a temperature of 140-145° C. The addition time is 3.2-3.6 hours. After the addition is completed, the mixture is reacted at 140-145° C. for 4-6 hours to obtain a pre-modified acrylate resin; S2, 120-130 parts of ethylene glycol ethyl ether, 100 parts of water-based epoxy resin, 0.5-0.7 parts of dimethylethanolamine, and 20-30 parts of dimethylol propionic acid are mixed, the temperature is raised to 110-120° C., and the reaction is performed for 5-7 hours to obtain a semi-open-ring epoxy resin; S3, mixing the pre-modified acrylate resin prepared in S1 and the semi-open-ring epoxy resin prepared in S2, heating to 130-135° C., reacting for 2-3 hours, cooling to 60-65° C., adding 50-60 parts of triethylamine, and obtaining a modified waterborne acrylic resin.

2. The water-based one-component container coating according to claim 1, characterized in that: The mixed monomers are isobornyl methacrylate, hydroxypropyl methacrylate and methacrylic acid in a weight ratio of 1: (1.2-1.4): (0.5-0.7).

3. The water-based one-component container coating according to claim 1, characterized in that: The preparation method of the modified waterborne epoxy resin comprises the following steps by weight: (1) Mix 30-32 parts of phenolic epoxy resin, 0.5-0.8 parts of tetra-n-butylammonium bromide and 0.1-0.2 parts of hydroquinone, raise the temperature to 90-95°C, and dropwise add 40-50 parts of a mixed solution of heptafluorobutyric acid and 12-15 parts of methacrylic acid for 1-2 hours. After the dropwise addition is completed, raise the temperature to 115-120°C and react for 5-7 hours to obtain a prepolymer; (2) Mix 35-40 parts of prepolymer and 5-10 parts of maleic anhydride, react at 95-100°C for 3-4 hours, add 5-8 parts of triethylamine, stir for 50-60 minutes, add 50-55 parts of deionized water, stir at 50-55°C for 2.0-2.5 hours, and cool to obtain a modified waterborne epoxy resin.

4. The water-based one-component container coating according to claim 1, characterized in that: The preparation method of the modified filler comprises the following steps by weight: (1) mixing nano-lanthanum oxide, nano-aluminum oxide and nano-silicon dioxide to obtain a mixed filler; (2) Mix 1 part of mixed filler, 8-10 parts of anhydrous ethanol and 0.1-0.3 parts of silane coupling agent KH570, stir and react at 60-65°C for 5-7h, filter, wash and dry to obtain silane-modified filler; (3) Mix 10-15 parts of anhydrous ethanol, 1 part of silane-modified filler, 0.03-0.05 parts of azobisisobutyronitrile, and 0.2-0.3 parts of glycidyl methacrylate, heat and stir at 60-65° C. for 7-9 hours, filter, wash, and dry to obtain a modified filler.

5. The water-based one-component container coating according to claim 4, characterized in that: The weight ratio of nano-lanthanum oxide, nano-aluminum oxide and nano-silicon dioxide is (1.3-1.5):1:(0.4-0.7).

6. The water-based one-component container coating according to claim 5, characterized in that: The particle size of nano-alumina is 15-20nm and the specific surface area is 150-200m 2 / g; the particle size of nano-silicon dioxide is 10-20nm, and the specific surface area is 70-100m 2 / g; the particle size of nano lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g.

7. The water-based one-component container coating according to claim 1, characterized in that: The anti-rust pigment is aluminum zinc phosphate.

8. The water-based one-component container coating according to claim 1, characterized in that: The coloring pigment is titanium dioxide.

9. The water-based one-component container coating according to claim 1, characterized in that: The cosolvent is dipropylene glycol methyl ether acetate.

10. A method for preparing a water-based one-component container coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Weigh each component according to its weight; (2) Add defoamer and dispersant into water under low-speed stirring and stir for 5-10 minutes; (3) Add coloring pigment, anti-rust pigment and modified filler under stirring, stir for 15-30 minutes after adding, and disperse at high speed. Stop dispersing after reaching the required fineness and transfer to the paint mixing tank; (4) Add the remaining components while stirring and stir for 0.5-1h to obtain a water-based one-component coating for containers.

Citation Information

Patent Citations

  • Epoxy-modified aqueous acrylic resin and aqueous vacuum film coating primer prepared from epoxy-modified aqueous acrylic resin

    CN107163256A

  • Waterborne environment-friendly coating material as well as preparation method and application thereof

    CN108359342A

  • Modified epoxy resin anticorrosion paint, and preparation method thereof

    CN109251632A

  • Water-based nano silicon dioxide salt-spray-resistant waterproof coating for steel structure and preparation method thereof

    CN112480788A

  • UV curing fluorine modified water-based epoxy resin and preparation method thereof

    CN113121792A